Integrasi Komunikasi Promosi Kesehatan dan Epidemiologi melalui Speaker Masjid dalam Upaya Penanggulangan Stunting - Iswadi, Muhamad Khalid; Fitrianingsi, Nur; Laelatunnufus, Alfiatmi; Julaikha, Siti (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Stunting is a global health issue that affects children’s quality of life, and its prevalence remains high in Indonesia, including in West Lombok Regency. This study aims to analyze the messages delivered through the integration of health promotion and epidemiology communication via mosque speakers in Karang Bongkot Village, as well as the role of mosque caretakers in supporting stunting prevention efforts. A qualitative case study approach was employed, with interviews conducted with mosque caretakers, pregnant and breastfeeding women, healthcare workers, and religious leaders. The findings revealed that the messages conveyed included the importance of balanced nutrition, exclusive breastfeeding, and routine health checkups. The mosque caretaker plays a crucial role in delivering information to the community, supported by healthcare workers and religious leaders who provide legitimacy to the messages. Community-based communication strategies through mosques are effective in raising awareness about stunting prevention. This study concludes that integrating health promotion communication through mosques can be an effective solution in addressing stunting in the community.